BURNOUT PADA PERAWAT DITINJAU DARI EFIKASI DIRI DAN DUKUNGAN SOSIAL DI RUMAH SAKIT âXYZâ DI SURAKARTA (Nurses Burnout in terms of Self Efficacy and Social Support at âXYZâ Hospital of Surakarta) - Lailani, Fereshti; Rifayani, Hastuti; Paramita, Metta (Universitas Sahid Surakarta, 2014)
The research was aim to find out the relationship between self-efficacy and social support with burnout among nurses. Proposed hypotheses were as followed: 1). burnout correlatedÂ withÂ self-efficacyÂ danÂ socialÂ support,Â 2).Â Self-efficacyÂ negativelyÂ correlated with burnout, the lower self-efficacy was, the higher was the burnout; 3) social support negativelyÂ correlatedÂ withÂ burnout,Â theÂ higherÂ socialÂ supportÂ was,Â theÂ lowerÂ wasÂ the burnout.Â ThisÂ researchÂ alsoÂ createÂ aÂ newÂ modelÂ ofÂ competenciesÂ inÂ aÂ wayÂ toÂ copeÂ the burnout happened, considered to nurses work load. TheÂ subjectÂ ofÂ theÂ researchÂ consistedÂ ofÂ 94Â nursesÂ ofÂ âXYZâÂ HospitalÂ of Surakarta. Data was collected through questionnaire method using burnout scales, self efficacy scales and social support scales.Â Statistical method used regression analysis with SPSS for Windows11.5.TheÂ resultsÂ showedÂ thatÂ thereÂ wasÂ significantÂ correlationÂ betweenÂ self-efficacy and social support with burnout (R= 0.743, F= 56.209, p < 0.05) and it contributed as much as 55.3Â %.Â Self-efficacyÂ hadÂ significantlyÂ negativeÂ correlationÂ withÂ burnoutÂ (t=Â -6.250 , p < 0.05). Social support also had significantly negative correlation with burnout (t= -3.106 , p<0.05).Key words: self-efficacy, social support, burnout